Efficacy and safety of emtricitabine/tenofovir alafenamide (FTC/TAF) vs. emtricitabine/tenofovir disoproxil fumarate (FTC/TDF) as a backbone for treatment of HIV-1 infection in virologically suppressed adults: subgroup analysis by third agent of a randomized, double-blind, active-controlled phase 3 trial*. Issue 3 (4th May 2017) - Post, Frank A.; Yazdanpanah, Yazdan; Schembri, Gabriel; Lazzarin, Adriano; Reynes, Jacques; Maggiolo, Franco; Yan, Mingjin; Abram, Michael E.; Tran-Muchowski, Cecilia; Cheng, Andrew; Rhee, Martin S.
Abstract : Background: FTC/TAF was shown to be noninferior to FTC/TDF with advantages in markers of renal and bone safety. Objective : To evaluate the efficacy and safety of switching to FTC/TAF from FTC/TDF by third agent (boosted protease inhibitor [PI] vs. unboosted third agent). Methods: We conducted a 48-week subgroup analysis based on third agent from a randomized, double blind study in virologically suppressed adults on a FTC/TDF-containing regimen who switched to FTC/TAF vs. continued FTC/TDF while remaining on the same third agent. Results: We randomized (1:1) 663 participants to either switch to FTC/TAF ( N = 333) or continue FTC/TDF ( N = 330), each with baseline third agent stratifying by class of third agent in the prior treatment regimen (boosted PI 46%, unboosted third agent 54%). At week 48, significant differences in renal biomarkers and bone mineral density were observed favoring FTC/TAF over FTC/TDF ( p < 0.05 for all), with similar improvements in the FTC/TAF arm in those who received boosted PI vs. unboosted third agents. At week 48, virologic success rates were similar between treatment groups for those who received a boosted PI (FTC/TAF 92%, FTC/TDF 93%) and for those who received an unboosted third agent (97% vs. 93%). Conclusions: In virologically suppressed patients switching to FTC/TAF from FTC/TDF, high rates of virologic suppression were maintained, while renal and bone safety parameters improved, regardless of whether participants were receiving a boosted PI or an unboosted third agent. FTC/TAF offers safety advantages over FTC/TDF and can be an important option as an NRTI backbone given with a variety of third agents.